Automating human interactions with the use of technology - Meira, Isaac Tadeu (Seven Editora, 2023)
The objective of this article is to demonstrate the applicability of chatbots in large companies, demonstrating, through an experimentation study, that the creation of a system that interacts with the user, in a humanized way, can add a lot in companies that today have their own departments to solve some problems that could be automated. In addition, this article has successful cases in various industries, using the same technology as chatbots, increasing profits, reducing expenses, transforming any interaction via computer into humanized service. To conclude, this article brings at its core, questions of how much machines They can replace human and personalized service, and this question has lasted throughout the development of this article, where we can put on the agenda, even implicitly, which professions can, in the future, be replaced by simple computer programs, where the greatest effectiveness is when the user cannot differentiate which is the computer and which is the human employee. DOI:https://doi.org/10.56238/sevened2023.006-039